Autoritarismo y ciudadanía: La Falta de juramento. Verdad y escritura en algunas obras de Elvira Hernández (La Bandera de Chile, Carta de viaje, Santiago Waria y Cuaderno de Deportes) - Francisca Rojas Bahamondes (Confluenze, 2013)
The article interprets the poetical and ethical parable in Elvira Hernández’s language, putting a part of her work as a Chilean lyric poet into the historical context of the military dictatorship (1973-1990). It appears to focus on its capability to reveal the hidden dynamics of power, in addition to its origins in the civic and authorial compromises in the speech act. In this analysis, she introduces into evidence a straight opposition against the authoritarian power, as well as its faculty to preserve parts of the collective memory and the perpetual violence experienced at a sensitive level.